The influence of religiosity, knowledge, and income on the decision of muzakki to pay zakat mal in Baitul Mal Aceh Tamiang - Syahri Ramayani; T, Saipul Hadi; Muhammad Uzair Zulkifly (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2023)
Abstract Objective - This study was conducted to determine the level of muzakki decision in paying zakat maal. Method - This research uses quantitative research. The population in this study was muzakki Baitul Mal Aceh Tamiang Regency, and the technique used in sampling was Non-Probability Sampling. The sample in this study amounted to 88 samples. The types of data used in this study used primary and secondary data. The analysis techniques used are data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing using the SPSS version 16 program. Findings - The results showed that simultaneously the variables of Religiosity, knowledge, and Income positively and significantly affected the behavior of paying mal zakat. Partially the religiosity variable had a positive and significant effect on the behavior of paying mal zakat, knowledge had a positive and significant effect on the behavior of paying mal zakat, and the income variable had a positive and significant effect on the behavior of paying mal zakat. The percentage of influence of Religiosity, knowledge, and income variables on the behavior of muzakki in paying zakat mal together is 59.2%. Limitations - This research is considered a cause-and-effect with a single observation object. Practical Implications - This research shows the need for additional research variables so that the decision of muzakki to pay maal Zakat in Baitul Mal Aceh Tamiang Regency can increase higher to increase the collection of zakat funds in Baitul Mal Aceh Tamiang Regency to maximize future distribution programs so that they can be distributed evenly and relatively to all people in Aceh Tamiang Regency.